Application of mind map can promote the health education effect of children with vasovagal syncope - Liu, Ping; Mei, Wanzhen; Zhou, Mengying; Zhao, Ting; Wang, Yuwen; Zou, Runmei; Wang, Cheng (Frontiers in Cardiovascular Medicine, 2023)
Objective To explore the effect of mind map on health education in children with vasovagal syncope (VVS). Methods In this prospective controlled study, 66 children with VVS (29 males, 10.38 ± 1.80 years) and their parents (12 males, 39.27 ± 3.74 years) who were hospitalized in the Department of Pediatrics, The Second Xiangya Hospital, Central South University from April 2020 to March 2021 were set as the control group. 66 children with VVS (26 males, 10.29 ± 1.90 years) and their parents (9 males, 38.65 ± 1.99 years) who were hospitalized in the same hospital from April 2021 to March 2022 were set as the research group. Traditional oral propaganda method was applied in the control group, and the health education method based on mind map was applied in the research group. The self-designed VVS health education satisfaction questionnaire and comprehensive health knowledge questionnaire were used to conduct on-site return visits to the children and their parents who had been discharged from the hospital for 1 month. Results There was no significant difference in age, sex, hemodynamic type of VVS, and the parental age, sex, education level between the control group and the research group (P > 0.05). Health education satisfaction score, health education knowledge mastery score, compliance score, subjective efficacy and objective efficacy in the research group were higher than those in the control group (P < 0.05). If the satisfaction score, knowledge mastery score, and compliance score increase by 1 point, the risk of poor subjective efficacy is reduced by 48, 91, and 99%, respectively, and the risk of poor objective efficacy is reduced by 44, 92, and 93%, respectively. Conclusions Application of mind map can improve the health education effect of children with VVS.